STUDENTS’ PERCEPTIONS ON LEARNING ENGLISH THROUGH MICROSOFT TEAMS - Fitria Nurkusumaningrum; Slamet Utomo; Nuraeningsih Nuraeningsih (JALL (Journal of Applied Linguistics and Literacy), 2022)
English is one of the subjects that has an important role in communication, because English is an international language used to communicate in various countries. Since the pandemic all activities have been carried out online, including learning activities. Many learning applications are used during online learning, one of them is Microsoft Teams. Microsoft Teams is a learning application that has very complete features. This research aims to describe students' perceptions of learning English through Microsoft Teams in class XI students at SMA 2 Kudus.  This research uses a qualitative research design with an open questionnaire instrument given to 50 students and interviews with 15 student. The results of this research indicate that the students of class XI at SMA 2 Kudus have a neutral perception of learning English through Microsoft Teams. This is evidenced by the fact that most students think that learning English through Microsoft Teams is effective and efficient, but they face several obstacles while using Microsoft Teams which causes them do not understand the material and choose face-to-face learning. From the results of this research, it is suggested that students pay more attention to the importance of learning English and motivate themselves to study harder.